THE IMPACT OF PHYSICAL ACTIVITY ON CHRONIC KIDNEY DISEASE: BENEFITS, SCIENTIFIC PROOFS, SAFETY, AND GUIDELINES FOR EXERCISE PRESCRIPTION - Bartłomiej Grodziński; Dominik Łepecki; Wiktoria Natalia Dzierzgowska; Martyna Niemczuk; Mateusz Korga; Angelika Kędzierska; Marta Kras; Maja Kuklo; Agata Karasiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Chronic Kidney Disease (CKD) is a significant global health issue characterized by progressive loss of kidney function, impacting quality of life and increasing the risk of morbidity and mortality. This paper explores the multifaceted role of physical activity in managing CKD, focusing on its benefits, safety considerations, and best practices for exercise prescription, based on systematic reviews of literature sourced from PubMed and Google Scholar. While physical activity has been shown to offer substantial benefits, such as improved cardiovascular outcomes, enhanced physical function, and reduced inflammation, safety concerns are paramount. These include potential risks associated with exercise intensity and its effects on kidney function and overall health. The paper also evaluates best practices for integrating exercise into CKD management, based on recent evidence and expert recommendations. Our findings suggest that regular physical activity is a crucial component of CKD management, with significant potential to improve patient outcomes. However, tailored exercise programs that account for individual patient conditions and disease stages are essential to maximize benefits and minimize risks. This review underscores the need for ongoing research and refined guidelines to optimize exercise interventions for CKD patients, ensuring safe and effective integration into standard care practices.